Correlation between Laboratory Turnaround Time in Pediatric Emergency Departement and Length of Stay - Pratiwi, Putu Diah; Wati, Dyah Kanya; Hartawan, I Nyoman Budi (UI Scholars Hub, 2018)
A quick and precise diagnosis is essential in hospital services, especially in the emergency department. In condition with high volume patients, perfomance of laboratory usually decreases. Studies which identify directly the delay of laboratory examinations in emergency department in relation to length of stay in wards have not been conducted. We did correlative study using secondary data obtained from medical records. Inclusion criteria was child, age range from 29 days to 12 years old who needed supporting laboratory examinations, directly admitted to wards or PICU after getting treatments in emergency department. Exclusion criteria was child with growth and developmental problem, malnutrition, immuncompromised condition, incomplete medical records data, and child died in the emergency department. Average patient in 2016 was 3,6 yeras old and in 2017 was 2 yeras old, mostly boys. Mostly with chief complaints of infections Analysis in 2017 showed correlation coefficient of 0.466 which means there was strong association between laboratory turnaround time and length of stay and statistically significant (p 0.03). multivariate analysis shown there was strong correlation between laboratory turnaround time and length of stay and if the predictive value increased by one unit, the length of stay would increase 6,5%.